2012
DOI: 10.11599/germs.2012.1025
|View full text |Cite
|
Sign up to set email alerts
|

Management of accidental exposure to HCV, HBV and HIV in healthcare workers in Romania

Abstract: The exposure events analysis in this study yielded similar results compared to other previous parallel studies. Minimizing risks to HCWs for acquisition of blood-borne pathogens and correct and rapid post-exposure prophylaxis treatment in case of exposure should be an integral part of the infection control and occupational health programs in all healthcare facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…On the contrary, Malka et al, in Romania, found that all HCWs who reported an exposure were tested at the day of the event and were followed at least once during the first year and after 12 months. 31 In our study, 96.9% of injured HCWs did not receive PEP. On the contrary, another study reported that PEP was not administered in only 5% of cases.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…On the contrary, Malka et al, in Romania, found that all HCWs who reported an exposure were tested at the day of the event and were followed at least once during the first year and after 12 months. 31 In our study, 96.9% of injured HCWs did not receive PEP. On the contrary, another study reported that PEP was not administered in only 5% of cases.…”
Section: Discussionmentioning
confidence: 50%
“…On the contrary, another study reported that PEP was not administered in only 5% of cases. 31 additionally, Himmelreich et al, found that, almost all employees with anti-HBs, of less than 100 IU/L at time of exposure, received HBV booster immunization within 48 h of their NSSIs. 1 Findings of the current research contradict what was reported during the interview with the head of Infection Control Unit at AMUH regarding the existence of adequate safety policies for the use of needles and sharps, and availability of post-exposure management including blood testing for the exposed HCWs at time of exposure and follow-up tests.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran 1.3% to 8.69% and in Romania 2% to 7% of the population are chronic HBV carriers, approximately. 1,2 Also, HBV is one of the occupational menaces for healthcare workers (HCW), the infection risk through exposure to blood and infectious body fluids being highest in this category. 3 The WHO estimates that per year 66,000 HBV infections take place in HCWs due to career exposure to percutaneous damages.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In Iran, a vaccination campaign was implemented in 1993; 5 it included HCWs and it encouraged all individuals at risk for HBV infection to get vaccinated against HBV. Despite a substantial decline in the incidence of occupationally-acquired HBV, residual infection in healthcare systems still exists due to both incomplete coverage of vaccination and nonresponsiveness to vaccine among HCWs.…”
mentioning
confidence: 99%